The impact of using generative artificial intelligence applications on developing digital educational content creation skills and the attitudes of female trainers and trainees at the Girls’ Technical College towards them - Alzughaibi, Imtinan Mohammed; Alfarani, Leena Ahmed (Journal of Educational and Psychological Sciences, 2025)
The research aimed to reveal the impact of using generative artificial intelligence applications on developing skills for creating digital educational content and the attitudes of female trainers and trainees at the Technical College for Girls towards these applications. The research followed a descriptive approach to measure attitudes and a quasi-experimental design. For the purposes of the research, an evaluation card was designed to assess skills in creating digital educational content and an attitude scale was created to measure the participants’ attitudes towards using generative artificial intelligence applications for developing skills in creating digital educational content. The sample consisted of 31 trainers and trainees from the Technical College for Girls, selected randomly in a single group that was exposed to the experimental treatment. Subsequently, measurement and evaluation tools were applied post-test during the first semester of the 1445 Hijri year. The research concluded that the participants’ attitudes towards using these applications in creating digital educational content were positive, and the results on the evaluation card were high, indicating that generative artificial intelligence applications played a significant role in developing digital content creation skills. The research provided recommendations and suggestions based on the findings, the most important of which was to focus on leveraging generative artificial intelligence and its applications in local training and educational institutions and in the creation of various digital content, alongside promoting technological culture and raising awareness about the positive effects of artificial intelligence in education.